Pengaruh Transparansi, Akuntabilitas Dan Partisipasi Masyarakat Terhadap pengelolaan Dana Desa. - Wulandari, Nimas Ayu; Sujatmika, Sujatmika (Badan Penerbitan Fakultas Pertanian Universitas Ratu Samban, 2024)
This research aims to examine the influence of transparency, accountability and community participation on village fund management in all villages in Sampung District, Ponorogo Regency. This research uses a quantitative approach which is collected through primary data in the form of questionnaires distributed to respondents. The sampling method used considerations from researchers, so that 60 respondents were obtained, namely village officials consisting of the Village Head, Village Secretary, Head of Financial Affairs, Head of Administrative and General Affairs, and Head of Planning Affairs, each of whom was adapted to the Village Government Organizational Structure. The analysis technique in this research uses multiple linear regression analysis. The results of this research show that transparency, accountability, community participation have an influence on village fund management.